Dysphemism as a Language Strategy for Expressing Emotional Intensity in Sabrina Carpenter’s Man’s Best Friend Album - Ruth Manurung; Cindy C. Nadeak; Helda H. Hia; Jesika P. Sitorus; Nurjasni Nurjasni; Meisuri Meisuri (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study examines the use of dysphemistic language in selected songs from Sabrina Carpenter’s Man’s Best Friend album. The research aims to identify the dysphemistic expressions found in the lyrics and to analyze how these expressions are linguistically constructed to convey emotional intensity and communicative meaning. The study applies a qualitative descriptive approach. The data consist of dysphemistic expressions collected from the selected song lyrics and classified according to the dysphemism categories proposed by Keith Allan and Kate Burridge. The analysis focuses on identifying the types of dysphemism and examining their function as a language strategy within the lyrical context. The findings indicate that dysphemistic expressions appear consistently in the lyrics and contribute to the expression of emotional tension and interpersonal conflict. These expressions also function as a stylistic device that shapes the tone and communicative impact of the songs. The study highlights the role of dysphemistic language as part of the expressive and stylistic resources used in contemporary pop music lyrics.